Molecular typing of the pneumococcus and its application in epidemiology in sub-Saharan Africa - Donkor, Eric S. (Frontiers in Cellular and Infection Microbiology, 2013)
Molecular typing of the pneumococcus has played a crucial role in understanding the epidemiology of the organism. However, most of what is known about molecular epidemiology of the pneumococcus pertains to the developed world. The brunt of pneumococcal infections is borne by sub-Saharan African countries, which makes epidemiological monitoring of the pneumococcus essential in this region of the world. This review paper focuses on molecular typing of the pneumococcus and what is known about epidemiology of the organism in sub-Saharan Africa based on the various typing methods. Several molecular typing methods are available for typing the pneumococcus and the major ones include multilocus sequence typing, multilocus enzyme electrophoresis, serotyping and DNA fingerprinting methods such as pulsed field gel electrophoresis and amplified fragment length polymorphism. Currently, multilocus sequence typing is the most suitable method for typing the pneumococcus. The pneumococcal population structure in sub-Saharan Africa appears to be quite different from that of the developed world, and pneumococcal serotype 1 related to the ST 618 clone and clones of the ST 217 clonal complex are responsible for outbreaks in sub-Saharan Africa.